If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + 30 = 3 + 15y Reorder the terms: 30 + 10y = 3 + 15y Solving 30 + 10y = 3 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 30 + 10y + -15y = 3 + 15y + -15y Combine like terms: 10y + -15y = -5y 30 + -5y = 3 + 15y + -15y Combine like terms: 15y + -15y = 0 30 + -5y = 3 + 0 30 + -5y = 3 Add '-30' to each side of the equation. 30 + -30 + -5y = 3 + -30 Combine like terms: 30 + -30 = 0 0 + -5y = 3 + -30 -5y = 3 + -30 Combine like terms: 3 + -30 = -27 -5y = -27 Divide each side by '-5'. y = 5.4 Simplifying y = 5.4
| 10y+30=3+15 | | 3x^2=2x^2+25 | | 4y+6(y-1)=54 | | x+y=x+1/12 | | (6x-25)+(6x+6)+(7x+2)+(15x-25)+(3x+3)+(5x-9)+(4x-14)+(5x-9)=1080 | | 6+z+3z-4= | | 0,34+6x=0,4x-8 | | (3v+1/5)^2 | | 5+2(6-2)^2/4 | | 12x^2+24x= | | 21x-5=13x+8 | | y-7=(x-3) | | 20=2(3x+4) | | (3x-6)+(6x-10)+(5x)+(3x+11)+90=720 | | X-20=20+20 | | -5(r+6)=-97 | | 2.3w=11.5 | | (4x-3)(3x+2)-(6x-7)(2x-5)=2 | | 8(7x-2)=96 | | b-2+4b=29 | | -16-1(6x-4)=6 | | X+34=29 | | 2x+3x-6=4 | | y-1=.7(x-4) | | 1/3(6p+9)=11 | | 10x+5-18x=7-5x-3 | | 3(4x+5)=21 | | 2(3x-1)=11+(8-x) | | 10(x+2)+6=96 | | 3x-5=12-4x | | 5x^2=41x-8 | | 13+3(4r-3)=-8 |